Interactive histology - Wingerd, Bruce D.; Paolini, Paul ([S.l.] : McGraw-Hill, 2000)
Contents : introduction to tissues, tissues forming the organ systems, selected scanning electron micrographs, problem set, glossary and self-quiz
System requirements : IBM-compatible computer, 486, 50 Mhz processor, 90 Mhz processor recommended, 16 MB RAM, 10 MB of available hard disk space, Windows 95, UNIX SVR4, 640 X480 X256 color display, CD-ROM drive
Keywords: Histology; Tissues